KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN AKURASI SHOOTING SSB PATRIOT MUDA KUOK - M. Riyadhi M. Riyadhi; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine how much the contribution of the explosive power of the leg muscles, the contribution of eye and foot coordination, the contribution of the explosive power of the leg muscles and the coordination of the eyes and feet with the shooting accuracy of the SSB Patriot Muda Kuok players. The study was conducted using a correlational research design which aims to determine how much the contribution of the independent variable, namely the leg muscle explosive power (X1) and eye and foot coordination (X2), to the dependent variable, namely the accuracy of the football shooting results (Y). As for the population in this study, all research objects, namely the Patriot football SSB players, which consisted of 25 people, namely Patriot Muda Kuok SSB players. Based on the results of the research that the author has described in the previous chapter, it can be concluded that the leg muscle explosive power has contributed to the shooting accuracy of the Patriot Muda Kuok SSB, which is 69.38%. Furthermore, the results obtained by eye and foot coordination contributed to the shooting accuracy of the Young Patriot Kuok SSB of 84.45%. There is a joint contribution between the explosive power of the leg muscles and the coordination of the eyes and feet with the shooting accuracy of the SSB Patriot Muda Kuok of 85%.Key Words: Contribution of leg muscle explosive power and eye and foot coordination withshooting accuracy